Not your mama’s knitting : - Dixon, Heather (Wiley, 2006)
This is knitting with attitude. Choose from nearly thirty designs, follow the simple directions, and knit fun, trendy items to dress yourself, your friends, your home, a baby, or even a pet. This guide covers must-know techniques, tools of the trade, customizing designs, and more. Get clicking and express yourself with hip, hyper-chic designs any fashionista would covet.